Firms' export decisions: Self-selection versus trial-and-error - Mohammad Movahedi; Kiumars Shahbazi (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
In this paper, a conceptual theoretical model is developed to better integrate various dimensions of the firms' decision to export. The model sheds light on the affirmations of the founding models of the 'new theory of international trade', in particular the role of productivity and sunk costs of exporting in the firms' export decision. It also takes into account two stylized facts that seem difficult to be reconciled with the implications of the founding models: 1) many domestic firms, regardless of their productivity level, enter foreign markets every year with little sales and cease all exporting activities in less than a year; 2) several of high-productivity firms choose to only serve their domestic market.
Keywords: F10; 330; firm heterogeneity; self-selection; sunk cost of exporting